The tasks of choosing the optimal operating conditions of oil pumping stations with the system approach - Yaremak, I. I. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The tasks of choice of the optimal modes of operations of the oil pumping stations are defined from the positions of the system approach. For the control of pumping aggregate two channels are used: current of excitation of drive synchronous engine and speed of its rotation. Solution of tasks of optimal control of the pumping aggregate work allows estimating the cost expenses on setting of one or another mode of the oil pumping station taking into account physical properties of pumping aggregate.